Comparing efficacies of various papain-based enzyme agents and 2.4% sodium hypochlorite gel in chemomechanical caries removal: a randomized controlled trial - M. H. D. Baraa Alsayed; Mawia Karkoutly; Hassan Achour; Souad Abboud (Nature Publishing Group, 2024)
Abstract Objective This study aimed to evaluate and compare the efficacies of Papacarie Duo gel, Brix 3000, Selecti-Solve gel, 2.4% sodium hypochlorite gel, and conventional rotary-mechanical method in caries removal and to evaluate the patient comfort. Methods It was a single-blinded, randomized, parallel-group, active-controlled trial with five arms. It was conducted at the Department of Restorative Dentistry and Endodontics, Damascus University. Seventy-five specimens were randomly allocated into five groups: chemomechanical caries removal (CMCR) using Selecti-Solve gel (G1), BRIX3000 (G2), Papacarie DUO gel (G3), or 2.4% sodium hypochlorite gel (G4), and caries excavation using conventional rotary-mechanical method (G5) (control group). The trial considered healthy patients aged 18-40. Permanent molars with class I carious lesions extending to the middle third of dentin with no pulpal and/or periodontal pathology were included. The efficacy of caries removal was considered the primary outcome measure, and the secondary outcome measures were treatment time, volumetric measurement of the cavity, and pain assessment. Results The majority (73.30%) of cases from BRIX3000 and conventional rotary-mechanical method groups showed complete caries removal (p = 0.982). The mean time of caries removal was the highest (17.45 ± 4.42) in the 2.4% sodium hypochlorite gel group (p < 0.05), and the lowest (6.33 ± 1.69) was in the conventional rotary-mechanical method group (p < 0.05). The mean cavity volume was the highest (18.97 ± 9.76) in the Papacarie DUO gel group, and the lowest (14.87 ± 4.76) was in the 2.4% sodium hypochlorite gel group (p = 0.506). The conventional rotary-mechanical group exhibited the highest mean score (5.40 ± 1.72) of pain (p < 0.05). However, the mean score (2.67 ± 1.11) of pain reported reduced in the BRIX3000 group. Conclusions CMCR agents could be a potential substitute for conventional rotary instrumentation methods, taking into account the long working time.